The reactivity of neurotransmitters and their metabolites towards various nitrogen-centered radicals: Experimental, theoretical, and biotoxicity evaluation. (December 2021) - Lončar, Aleksandar; Negrojević, Luka; Dimitrić-Marković, Jasmina; Dimić, Dušan
Abstract: In the past few years, there has been a certain interest in nitrogen-centered radicals, biologically important radicals that play a vital role in various processes and constitute many important biological molecules. In this paper, there was an attempt to bridge a gap in the literature that concerns the antiradical potency of monoamine neurotransmitters (dopamine, epinephrine, and norepinephrine) and their metabolites towards these radicals. The most probable radical quenching mechanism was determined for each radical out of three common mechanisms, namely Hydrogen Atom Transfer (HAT), Single Electron Transfer followed by the Proton Transfer (SET-PT), and Sequential Proton Loss Electron Transfer (SPLET). Marcus' theory was then used to determine the reaction rates for the electron transfer process. SPLET was the most probable mechanism for both reactions with the aminyl and hydrazyl radicals, while HAT and SPLET were plausible mechanisms for reactions with the imidazolyl radical. Special emphasis was put on the investigation of the substituent effect on the preferred mechanism. The necessity of both thermodynamic and kinetic parameters for the comparison of the antiradical potency of compounds was discussed. The same methodology was applied for the theoretical investigation of the reactivity towards DPPH ⦁, a member of the hydrazyl radicals. An ecotoxicity analysis was performed to assess the impact the investigated radicals have on the ecosystem. Except for histidine, every other neutral form was either toxic or highly toxic to some of the analyzed marine organisms. Graphical Abstract: ga1 Highlights: SPLET is the dominant mechanism for scavenging of aminyl and hydrazyl radicals. HAT and SPLET are plausible mechanisms for scavenging of imidazolyl radicals. Structural moieties important for DPPH⦁-scavenging activity were determined. Single electron transfer reduction of DPPH⦁ is diffusion controlled. Most of N-centered radicals belong to the groups of harmful and toxic substances.